2019
DOI: 10.1007/s00262-019-02344-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel circulating tumor cell-based blood test for the assessment of PD-L1 protein expression in treatment-naïve, newly diagnosed patients with non-small cell lung cancer

Abstract: We evaluated the analytical and clinical performance of a novel circulating tumor cell (CTC)-based blood test for determination of programmed death ligand 1 (PD-L1) protein expression status in real time in treatment-naïve non-small cell lung cancer (NSCLC) patients. CTCs were detected in 86% of patients with NSCLC (I–IV) at the time of diagnosis, with a 67% PD-L1 positivity rate (≥ 1 PDL + CTC). Among 33 NSCLC patients with PD-L1 results available via both tissue immunohistochemistry (IHC) and CTC assays, 78.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
(48 reference statements)
0
19
0
1
Order By: Relevance
“…PD-L1 expression on CTCs has been previously reported in NSCLC [ 58 , 59 , 60 , 61 , 62 ]. Interestingly, the detection of PD-L1 + CTCs was associated with poor prognosis in patients treated with chemotherapy [ 60 ], whereas it was not predictive of survival in those treated with anti-PD-1 agents [ 55 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 expression on CTCs has been previously reported in NSCLC [ 58 , 59 , 60 , 61 , 62 ]. Interestingly, the detection of PD-L1 + CTCs was associated with poor prognosis in patients treated with chemotherapy [ 60 ], whereas it was not predictive of survival in those treated with anti-PD-1 agents [ 55 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following filtration, membranes were washed with PBS and WFI, air-dried at RT, and stored at −20 °C. The membrane spots ( n = 10), each one corresponding to 1 mL whole blood, were individually cut out and immobilized on 10 glass slides using adhesive ribbon to be further stained and analyzed by microscopy, as previously described by Pailler et al [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Although the entire ISET membrane can be stained and/or immobilized on a single slide, we did not select this procedure since it required larger volumes of antibody solutions compared to the staining of individual spots (a minimum of 2 mL vs 100 μL per spot to a final volume of 1 mL, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, testing for PD-L1 in the blood (liquid biopsy) and in circulating tumor cells may give a better idea about the tumor and will be easily accessible for repeated testing and patient monitoring. 23 , 24 Furthermore, it was reported that PD-L1 detection in peripheral blood was associated with worse survival of NSCLC, 25 even in patients treated with checkpoint inhibitors. 26 The techniques and use of liquid biopsy to evaluate biologic markers for immunotherapy including checkpoint inhibitors has great potential because of its convenience, safety, cost effectiveness, and ability to be performed repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the evaluation of PD-L1 expression on CTCs by immunofluorescence, reporting a variable grade of concordance with tissue PD-L1 IHC expression [49,52,53,56]. Interestingly, increase in PD-L1+ CTCs during treatment with ICIs seems associated with disease progression [52,53] and might represent a potential minimally invasive biomarker of resistance that can assist conventional radiographic assessment in those cases of uncertain progression (pseudo-progression or mixed response).…”
Section: Blood Sample Tmb and Pd-l1mentioning
confidence: 99%